2003
DOI: 10.1046/j.1365-294x.2003.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for deep phylogenetic divergence in Mandrillus sphinx

Abstract: Mandrills (Mandrillus sphinx) are forest primates indigenous to western central Africa. Phylogenetic analysis of 267 base pairs (bp) of the cytochrome b gene from 53 mandrills of known and 17 of unknown provenance revealed two phylogeographical groups, with haplotypes differentiated by 2.6% comprising seven synonymous transitions. The distribution of the haplotypes suggests that the Ogooué River, Gabon, which bisects their range, separates mandrill populations in Cameroon and northern Gabon from those in south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 23 publications
(58 reference statements)
6
81
1
Order By: Relevance
“…: A signal of recombination was detected in mtDNA of papionin monkeys (Piganeau et al 2004;Tsaousis et al 2005), including M. nemestrina (R. Setyadji, B. Suryobroto, T. Watanabe, and O. Takenaka, unpublished data; Evans et al 1999), Sulawesi macaques (Evans et al 1999), baboons (Newman et al 2004), and mandrills (Telfer et al 2003). After correction for multiple tests, one of four indirect tests for recombination used by Piganeau et al (2004) support recombination in the mtDNA data in this study from Borneo M. nemestrina (probability of the null hypothesis of no recombination (P no recomb ) ¼ 0.216, 0.015, 0.768, and .0.001 according to LDr 2 , LDD9, geneconv, and Max x 2 statistic tests).…”
Section: Tablementioning
confidence: 99%
“…: A signal of recombination was detected in mtDNA of papionin monkeys (Piganeau et al 2004;Tsaousis et al 2005), including M. nemestrina (R. Setyadji, B. Suryobroto, T. Watanabe, and O. Takenaka, unpublished data; Evans et al 1999), Sulawesi macaques (Evans et al 1999), baboons (Newman et al 2004), and mandrills (Telfer et al 2003). After correction for multiple tests, one of four indirect tests for recombination used by Piganeau et al (2004) support recombination in the mtDNA data in this study from Borneo M. nemestrina (probability of the null hypothesis of no recombination (P no recomb ) ¼ 0.216, 0.015, 0.768, and .0.001 according to LDr 2 , LDD9, geneconv, and Max x 2 statistic tests).…”
Section: Tablementioning
confidence: 99%
“…Although palynological and biogeographical data have been used to infer forest refugia (11)(12)(13)(14)(15)(16), their precise location and role in Pleistocene diversification is controversial. Several molecular studies suggest that refugia may have played an important role in structuring montane birds (17)(18)(19), primates (20)(21)(22), and trees (23). However, other forest species such as chimpanzees (24)(25)(26) and elephants (27,28) show relatively weak regional genetic structure, suggesting that wideranging and/or savannah-tolerant species may be poor indicators of range changes in tropical forest cover.…”
mentioning
confidence: 99%
“…For both Gorillas (Gorilla gorilla; [45,46]) and Mandrills (Mandrillus sphinx; [47]) phylogeographic studies based on mtDNA (for both species) and microsatellite (only for Gorilla) markers have shown that rivers hamper gene flow among populations and have a major role in partitioning the species diversity. For Mandrills, the Ogooué river (Gabon) separates populations in Cameroon and northern Gabon from those in southern Gabon [47].…”
Section: Rivers Are Playing a Major Role In Genetic Differentiation Fmentioning
confidence: 99%
“…For Mandrills, the Ogooué river (Gabon) separates populations in Cameroon and northern Gabon from those in southern Gabon [47]. For Gorilla, rivers are more permeable and allow limited admixture among populations separated by waterways [45].…”
Section: Rivers Are Playing a Major Role In Genetic Differentiation Fmentioning
confidence: 99%
See 1 more Smart Citation